Shakespeare and Contemporary Irish Literature
XIII, 258 p.
Keywords: This book shows that Shakespeare continues to influence contemporary Irish literature, through postcolonial, dramaturgical, epistemological and narratological means. International critics examine a range of contemporary writers including Eavan Boland, Marina Carr, Brian Friel, Seamus Heaney, John McGahern, Frank McGuinness, Derek Mahon and Paul Muldoon, and explore Shakespeare’s tragedies, histories and comedies, as well as his sonnets. Together, the chapters demonstrate that Shakespeare continues to exert a pressure on Irish writing into the twenty-first century, sometimes because of and sometimes in spite of the fact that his writing is inextricably tied to the Elizabethan and Jacobean colonization of Ireland. Contemporary Irish writers appropriate, adopt, adapt and strategize through their engagements with Shakespeare, and indeed through his own engagement with the world around him four hundred years ago.